2021
DOI: 10.1002/pat.5489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diazonium‐induced surface grafting on PES NF membrane fouling reduction in algal‐rich water treatment

Abstract: The algae bloom phenomenon incurs a major challenge to conventional drinking water treatment processes due to the discharges of a large amount of intracellular pollutant and odor compounds in the water sources. Membrane processes have been considered as promising technologies to treatment of algal‐rich water due to complete algal cell rejection however, its application has been limited by membrane fouling. In this work, the high‐performance loose antifouling PES NF membranes were fabricated using diazonium‐ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…The antifouling function of membranes is related to three surface characteristics, including hydrophilicity, surface roughness, and surface charge . Studies have shown that 2D materials with a charged surface and hydrophilicity would have great antifouling and antibacterial properties, which is important for industrial applications. Graphene, in particular, exhibits significant cytotoxicity toward bacteria .…”
Section: Research States Of Large-scale 2d Ion-selective Membranes An...mentioning
confidence: 99%
“…The antifouling function of membranes is related to three surface characteristics, including hydrophilicity, surface roughness, and surface charge . Studies have shown that 2D materials with a charged surface and hydrophilicity would have great antifouling and antibacterial properties, which is important for industrial applications. Graphene, in particular, exhibits significant cytotoxicity toward bacteria .…”
Section: Research States Of Large-scale 2d Ion-selective Membranes An...mentioning
confidence: 99%